Sabellian demonstratives : forms and functions - Dupraz, Emmanuel (Brill's studies in Indo-European languages & linguistics, 2012)
This book describes the semantic, syntactic, and pragmatic features of Sabellian demonstratives. It contains new hypotheses on the epigraphic genres in Republican Italy and a reconstruction of these grammatical items' Italic origins based on typological principles.